Pequenos incêndios por toda a parte a figuração das mulheres contemporâneas do romance à minissérie - Moura, Sandra Mônica do Nascimento (Universidade Federal de São Carlos, 2025)
This thesis investigates how the position of women in the contemporary context is addressed by Celeste Ng in her novel Little Fires Everywhere (2017) and how this narrative is revisited in its homonymous adaptation in miniseries format (2020). Celeste Ng employs a plot centered on family conflicts to explore themes such as gender and social roles. The aim is to give women a voice, emphasizing the contrasts between her female characters. Based on this book, the production company Hello Sunshine created a miniseries (with Celeste Ng’s collaboration in writing the script), incorporating additional issues such as racism and sexuality. The purpose of this thesis is to investigate how female characters are reimagined in this television adaptation. To achieve this, the study draws on cultural studies, focusing on key aspects of the contemporary world: the representation of minorities in connection with the oppression of women, patriarchal society from a postmodern perspective, and the dissonances of language as a means of highlighting the various ways in which women are compelled to remain silent. Ultimately, the thesis is grounded in the aesthetic construction of works from a female perspective, fostering the formation of identity and the construction of otherness for the reader/viewer.

Esta tesis investiga cómo la posición de la mujer en el contexto contemporáneo es tratada por Celeste Ng en su novela Pequeños fuegos por todas partes (2017) y cómo esta narrativa es retomada en la versión homónima en formato de miniserie (2020). Celeste Ng utiliza una trama de problemas familiares para discutir temas como el género y los roles sociales. El objetivo es dar voz a las mujeres, trabajando el contraste entre sus personajes femeninos. A partir de este libro, la productora Hello Sunshine creó una miniserie (con la colaboración de Celeste Ng en la escritura del guion), añadiendo otros temas, como el racismo y la sexualidad. El propósito de la tesis es investigar cómo se recrean los personajes femeninos en esta narrativa televisiva. Para lograrlo, el estudio se apoya en los estudios culturales y se centra en las particularidades contemporáneas: el tratamiento dado a las minorías en relación con la opresión de las mujeres, la sociedad patriarcal bajo un sesgo posmoderno y las disonancias del lenguaje como forma de indicar las múltiples maneras en que las mujeres se ven obligadas a silenciarse. Finalmente, la tesis se ancla en la construcción estética de las obras a través de la mirada femenina, promoviendo la formación de identidad y la construcción de alteridad del lector/espectador.
Little fires everywhere the portrayal of contemporany women from novel to miniseries
Keywords: Pequenos incêndios por toda a parte; Série televisiva; Estudos culturais; Pós-modernidade; Feminismos; Little fires everywhere; Television series; Cultural studies; Postmodernity; Feminisms; Pequeños fuegos por todas partes; Series de televisión; Estudios culturales; Posmodernidad; Feminismos; LINGUISTICA, LETRAS E ARTES::LETRAS::LITERATURA COMPARADA; LINGUISTICA, LETRAS E ARTES::LETRAS::TEORIA LITERARIA; LINGUISTICA, LETRAS E ARTES::LETRAS::LITERATURAS ESTRANGEIRAS MODERNAS